Radiocontrast-induced nephropathy is attenuated by autophagy through regulation of apoptosis and inflammation. (July 2016) - Ko, Gang Jee; Bae, So Yeon; Hong, Yu-Ah; Pyo, Heui Jung; Kwon, Young Joo
Radiocontrast-induced nephropathy (RCN) is the third most common cause of acute renal failure among inpatients. Although the number of patients undergoing exams using radiocontrast is increasing, little progress has been made for RCN treatment. The pathophysiology of RCN is known as tubular injury due to oxidative stress. As autophagy regulates cellular damage under stressful conditions, we investigated the role of autophagy in RCN. RCN was induced in male C57BL/6 J mice by intraperitoneal injection of iohexol, and 3-methyladenine (3-MA) was used as an autophagy inhibitor. Tubular injury caused by iohexol was also examined in vitro using rat tubular cells (NRK-52E). Increased autophagy after iohexol administration was demonstrated by the increase of light chain 3-II in the damaged kidney tubules both in vivo and in vitro. Serum creatinine and tubular injury were significantly increased at 24 h after iohexol treatment, as compared to control group. Further they worsened with autophagy inhibition by 3-MA. In vitro studies also demonstrated that decreased cell viability by iohexol was aggravated with 3-MA pretreatment. Malondialdehyde measured for oxidative stress was increased by iohexol, and it was accentuated by autophagy inhibition, which resulted in increase of cytochrome c . Apoptosis, increased by iohexol treatment, was augmented with autophagy inhibition. Macrophage infiltration and increase of monocyte chemotactic protein-1 in kidneys were induced by iohexol, and it was aggravated with autophagy inhibition. This study showed that autophagy was involved with the pathophysiology of RCN, and the role of autophagy in modulation of apoptosis, oxidative stress, and inflammatory cell infiltration was supposed as mechanisms mitigating RCN.